1995
DOI: 10.1209/0295-5075/32/7/010
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Non-Collinear Spin Structures in Fe/Cr(001) Superlattices

Abstract: We have studied the non-collinear interlayer exchange coupling in Fe/Cr(001) superlattices as a function of growth temperature using polarized neutron reflectometry with exit beam polarization analysis. We confirm that the occurrence of non-collinear spin structures is correlated with long-range lateral Cr thickness fluctuations, which, in turn, depend on the growth temperature. We find surprisingly strong coupling between the Fe layers. We explain our data using the recently proposed proximity magnetism model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 20 publications
6
32
0
Order By: Relevance
“…A set of domains with partly parallel and partly antiparallel alignment is likely to coexist. 20 Borchers et al 12 reported such a coexistence, but it could not be restored after demagnetization. In contrast, our results show the presence of a stable remanent state with coexistent small and large domains, because we measure our samples after numerous field cycles.…”
Section: Discussionmentioning
confidence: 98%
“…A set of domains with partly parallel and partly antiparallel alignment is likely to coexist. 20 Borchers et al 12 reported such a coexistence, but it could not be restored after demagnetization. In contrast, our results show the presence of a stable remanent state with coexistent small and large domains, because we measure our samples after numerous field cycles.…”
Section: Discussionmentioning
confidence: 98%
“…6,17,19 We performed polarized-neutron reflectivity measurements at the V6 beamline of the Hahn-Meitner Institut in Berlin. The incoming neutrons had a wavelength of = 0.466 nm and were polarized spin down by means of a supermirror.…”
Section: Polarized-neutron Reflectivitymentioning
confidence: 99%
“…The observation of non-collinear spin structures in Fe/Cr [202,206,207,208] Other research directions for transition-metal multilayers include studies of hydrogen loading in Fe/Nb [216,217] and Fe/V [218]. Due to differences in the hydrogen solubilities of the component materials, hydrogen goes exclusively into the nonmagnetic interlayers, and the concentration can be reversibly tuned by changing hydrogen pressure.…”
Section: Giant Magnetoresistive Heterostructuresmentioning
confidence: 99%